2015
DOI: 10.1188/15.cjon.19-02ap
|View full text |Cite
|
Sign up to set email alerts
|

A Culture of Avoidance: Voices From Inside Ethically Difficult Clinical Situations

Abstract: The authors found that many healthcare providers remain silent about ethical concerns until a precipitating crisis occurs and ethical questions can no longer be avoided. Patients, families, nurses, and physicians tended to delay or defer conversations about prognosis and end-of-life treatment options. Individual, interactional, and system-level factors perpetuated the culture of avoidance. These included the intellectual and emotional toll of addressing ethics, differences in moral perspectives, fear of harmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…In our study, the supervision setting provided opportunities to release and support repressed emotions, consistent with thoughts about supervision, burnout and health. Pavlish, Brown-Saltzman, Fine and Jakel [34] found that many healthcare employees avoid talking about ethical problems because of factors such as fear of harming relationships, lack of continuity in care and lack of shared decision-making. They meant that this avoidance could lead to moral distress and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the supervision setting provided opportunities to release and support repressed emotions, consistent with thoughts about supervision, burnout and health. Pavlish, Brown-Saltzman, Fine and Jakel [34] found that many healthcare employees avoid talking about ethical problems because of factors such as fear of harming relationships, lack of continuity in care and lack of shared decision-making. They meant that this avoidance could lead to moral distress and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible for the nurse practicing today to avoid ethical dilemmas and conflicts. Pavlish, Brown‐Saltzman, Fine, and Jakel () found that healthcare providers may remain silent about ethical concerns because of a culture of avoidance. This may impact relationships, cause an emotional toll for the staff, and create issues with continuity of care and shared decision making.…”
Section: Background and Significancementioning
confidence: 99%
“…[20] Conceptually, the nurse, as part of the professional community, should stick to the idea of patient-centred care in order to meet the patient where he or she is, whether that be hospital, clinic, nursing home, hospice or home [12]. Further, all of us managing cancer patients need to be honest about prognosis and treatment limitations, because patients can make better decisions when they know what's going on-even if the reality is difficu to hear [6]. Nowadays, experienced nurses need to take reign of leadership roles in nursing practice, teaching, research and service [5].…”
Section: Resultsmentioning
confidence: 99%
“…Oncology and palliative care nurses ofte encounter ethically difficu situations, and as a result more moral distress than other specialists [6]. Also, nurses spend more time with patients than other members of the care team, and therefore have a unique opportunity to know what's important to patients and to help them navigate decisions involved in their treatment [7].…”
Section: Ethical and Moral Considerationsmentioning
confidence: 99%